2020
DOI: 10.1111/vec.12948
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of caval syndrome during initial hemodynamic stabilization in dogs with heartworm disease

Abstract: ObjectiveTo report on the spontaneous resolution of caval syndrome in 5 dogs selected for their response to medical stabilization prior to scheduled heartworm extraction.Series summaryFive dogs with heartworm caval syndrome were treated with sildenafil, fluid, and supplemental oxygen therapy. Moreover, 4 of 5 dogs were also administered pimobendan to achieve hemodynamic stabilization in preparation for percutaneous heartworm extraction. Spontaneous heartworm migration back into the pulmonary arteries was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…42,47,48 Migration of worms from the right heart back into the pulmonary arteries occurs after induction of anesthesia for heartworm extraction and with stabilization prior to heartworm extraction, and is associated with the administration of pimobendan and sildenafil. 1,41,49 Nine dogs in our study had intracardiac heartworms at presentation despite receiving phosphodiesterase inhibitors (eg, pimobendan, sildenafil), similar to a previous report. 1 Pimobendan and sildenafil have vasodilatory effects through phosphodiesterase inhibition, while pimobendan also is a positive inotrope able to increase cardiac output.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…42,47,48 Migration of worms from the right heart back into the pulmonary arteries occurs after induction of anesthesia for heartworm extraction and with stabilization prior to heartworm extraction, and is associated with the administration of pimobendan and sildenafil. 1,41,49 Nine dogs in our study had intracardiac heartworms at presentation despite receiving phosphodiesterase inhibitors (eg, pimobendan, sildenafil), similar to a previous report. 1 Pimobendan and sildenafil have vasodilatory effects through phosphodiesterase inhibition, while pimobendan also is a positive inotrope able to increase cardiac output.…”
Section: Discussionsupporting
confidence: 87%
“…Dogs with severe heartworm disease that do not have evidence of hemolysis (including pigmenturia) can have clinical signs attributed to PH and right heart failure. 8,20,41 All dogs with a murmur and ascites in this study had evidence of PH, a finding that has been previously reported. 42 Dogs with intracardiac heartworms with low worm burdens that do not have active hemolysis might benefit from medical therapy as opposed to manual extraction.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…LUS and the global FAST a approach including thoracic FAST echocardiography views are most often performed with the patient standing and can be done with minimal distress and handling 32,35–37,41 . Interestingly, the transient and possibly complete resolution of caval syndrome in case 2 has been recently described in dogs being treated with pimobendan and other supportive measures 42 …”
Section: Discussionmentioning
confidence: 99%